Treatment of Myofascial Triggerpoints: A Comparison of “Spray and Stretch” and “Postisometric Relaxation” - Loosberg, B.; Brand, C.; Smolenski, U. C. (Physikalische Medizin, Rehabilitationsmedizin, Kurortmedizin, 2016)
Purpose: Referred pain from myofascial trigger points (MTrP) frequently can be found as the underlying condition in patients presenting with back pain, joint pain, or headache. The purpose of this trial was to compare the pain reduction of postisometric relaxation therapy (PIR) and spray and stretch therapy (SAS).Materials and Methods: Outpatients (24 female and 3 male) with at least one active MTrP were randomised to either SAS or PIR therapy. In both groups, every participant received 3 treatment sessions. The pressure pain threshold (PPT) was measured. Additionally, the pain level was rated by the patient using a visual analogue scale (VAS). The primary outcome was the difference in PPT at follow up after 3–4 weeks (t4) and time of randomisation (t0). As an exploratory data analysis PPT values and VAS ratings before and after each treatment session and VAS ratings at t0 and t4 have been evaluated.Results: The mean change in PPT was +22.1 kPa (SD 70.3 kPa) in the SAS group and −25.6 kPa (SD 80.5 kPa) in the PIR group. There was no significant difference between these mean values (p=0.1146). Hence no difference between these treatment options could be found. Also, the exploratory data analysis of PPT and VAS values did not suggest a difference between SAS and PIR treatments. In both groups, some patients worsened and some improved. In some cases PPT measurements and VAS ratings were inconsistent.Discussion: No difference was found between SAS and PIR, but the number of patients evaluated may have been too small to show an existing difference between the 2 treatment options. We included patients with acute myofascial pain as well as patients with chronic myofascial pain. They may react differently to treatment and should probably be evaluated separately. There may be a bias due to the change of the examiner in our trial. We can not explain the majority of women presenting with myofascial pain but this is consistent with former studies.Conclusions: Further research is necessary to reveal if either PIR or SAS therapy is more appropriate in terms of pain reduction. Patients with chronic pain and those with acute pain should be evaluated separately.
Keywords: trigger points; spray and stretch; postisometric relaxation